2001
DOI: 10.5334/ijic.21
|View full text |Cite
|
Sign up to set email alerts
|

Pastoralist health care in Kenya

Abstract: Health care for the Kenyan pastoralist people has serious shortcomings and it must be delivered under difficult circumstances. Often, the most basic requirements cannot be met, due to the limited accessibility of health care provisions to pastoralists. This adds major problems to the daily struggle for life, caused by bad climatic circumstances, illiteracy and poverty.We argue that strong, integrated and community based primary health care could provide an alternative for these inadequacies in the health syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…However, this median distance was over two fold higher for nomadic pastoralists (36 km) than agro-pastoralists (16 km). Similar distance to health facilities was reported from pastoralists in northern Kenya [ 28 ]. Widespread poverty compounded with resource allocation bias in many African countries resulted in concentration of investment in urban areas, despite the fact that large proportions of their population are rural.…”
Section: Discussionsupporting
confidence: 73%
“…However, this median distance was over two fold higher for nomadic pastoralists (36 km) than agro-pastoralists (16 km). Similar distance to health facilities was reported from pastoralists in northern Kenya [ 28 ]. Widespread poverty compounded with resource allocation bias in many African countries resulted in concentration of investment in urban areas, despite the fact that large proportions of their population are rural.…”
Section: Discussionsupporting
confidence: 73%
“…This is the first study to examine issues around access and attitudes to HPV vaccine in hard-to-reach communities. Nairobi slums and Maasai nomadic pastoralist communities represent populations that may be difficult to reach for an adolescent/pre-adolescent health intervention for a number of reasons, including mobility, difficulty accessing communities to offer services, availability to receive vaccine, school absenteeism and drop-out, and early age of sex and marriage[ 11 14 ]. Despite this, and, in common with other sub-Saharan African populations[ 15 ], a general lack of knowledge and awareness about cervical cancer and the HPV vaccine, there was considerable interest in receiving HPV vaccination in these communities, with many participants indicating they would support vaccination if adequate and appropriate information was available and efforts were made to address concerns and rumours.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that agro-pastoralist communities in remote areas have difficulty accessing FHFs resulting in the communities patronizing informal health facilities (IHFs) (Duba et al, 2001;Caulfield et al, 2016). However, Cheikhyoussef et al (2011) argue that traditional knowledge of plant species as medicines and traditional views on causes of diseases compel agro-pastoralists to rely more on traditional treatments.…”
Section: Introductionmentioning
confidence: 99%